Inactivation of Polyomavirus SV40 as Surrogate for Human Papillomaviruses by Chemical Disinfectants - Martin Hufbauer (MDPI AG, 2021)
Human papillomaviruses (HPV) are non-enveloped DNA viruses infecting cutaneous and mucosal squamous epithelia. Sexually transmitted HPV-types that are carcinogenic to humans such as HPV16 can induce cervical and other anogenital cancers. Virus transmission through fomites such as inadequately disinfected gynecological equipment is a further potential transmission route. Since HPV cannot be easily grown in cell culture, polyomavirus SV40 has been used as a surrogate virus when testing the virucidal activity of chemical disinfectants. So far, studies that have compared the virucidal activity of different disinfectants against HPV and SV40 are lacking. Here, we evaluated the susceptibility of HPV16 pseudovirus and SV40 to seven active biocidal substances using quantitative suspension tests. Ethanol, glutaraldehyde (GTA), dodecyldipropylentriamin (DPTA), and ortho-phthalaldehydes (OPA) were able to reduce the infectivity of HPV16 pseudovirus >99.99% after 5 min. In contrast, isopropanol, peracetic acid (PAA), and quaternary ammonium compounds with alkylamines (QAC) only led to a slight or no reduction in infectivity. Concerning SV40, only GTA (60 min contact time), PAA, and OPA had virus-inactivating effects. In conclusion, the virucidal activity of three out of seven disinfectants tested was different for HPV16 pseudovirus and SV40. In this study, SV40 was shown to be a reliable surrogate virus for HPV when testing isopropanol-, GTA-, QAC-, and OPA-based disinfectants.